The use of proton pump inhibitors is positively associated with osteoporosis in postmenopausal women in Germany. (2nd September 2016) - Jacob, L.; Hadji, P.; Kostev, K.
Abstract: Objectives: To analyze the association between the use of proton pump inhibitors (PPIs) and osteoporosis in German postmenopausal women. Methods: This study included 3092 women with osteoporosis and 3092 women without osteoporosis. Cases and controls were matched on the basis of age, health insurance, index year, and physician. The main outcome of the study was the risk of osteoporosis dependent on predefined risk factors. Gastrointestinal disorders potentially associated with osteoporosis were determined. The presence of PPIs including the duration of therapy was also assessed. Multivariate logistic regression models were fitted with osteoporosis as a dependent variable. Results: The mean age was 72.3 years; 5.6% of both osteoporosis patients and controls had private health insurance coverage. Gastrointestinal disorders occurred significantly more frequently in osteoporosis patients than in controls. The use of PPI drugs was also significantly more common in osteoporosis patients than in matched controls. Osteoporosis development was found to be associated with disorders of the esophagus (odds ratio (OR) 1.19, p  = 0.013) and gastritis/duodenitis (OR 1.14; p  = 0.045). Interestingly, the use of PPIs also led to an increase in the risk of developing osteoporosis (OR 1.62; p  < 0.001). Finally, the odds of being diagnosed with osteoporosis increased with the duration of PPI therapy from 1.58 for 1 year of therapy or less to 1.72 for at least 5 years of treatment. Conclusions: The use of PPIs was a risk factor for osteoporosis and this risk increased with therapy duration in German women. Esophagus disorders and gastritis/duodenitis also increased the risk of developing this chronic condition.